Taking Stock of Social Sustainability and the U.S. Beef Industry - Hannah Gosnell (MDPI AG, 2021)
This paper presents the results of a study of social sustainability in the U.S. beef industry with a focus on the pre-harvest, cattle ranching portion of the industry. Using an integrative literature review and interviews with fifteen thought leaders in the field, we synthesize key indicators of social sustainability and provide a framework to be used in analyzing social sustainability in the pre-harvest beef industry. We identify six themes that are critical to social sustainability: human health; learning/adaptation; community relations; equity and inclusion; land ownership, tenure, and succession; and industry structure. However, our results also indicate that social sustainability as a term is insufficient for representing the positive futures desired by ranchers and that quantifiable indicators and metrics are not able to capture some of the subjective qualities of social sustainability. There is a need for future research that builds on these ideas and explores alternative future scenarios for the U.S. beef industry by engaging more diverse perspectives.